Student's mobile phone habitual behaviour for academic purposes: empirical evidence from a higher learning institute in Malaysia - Mahat, Jazihan; Ibrahim, Norasyikin; Mohd Ayu, Ahmad Fauzi (Human Resource Management Academic Research Society, 2023)
Mobile phones have become essential tools in educational environments, as they can significantly influence students’ learning achievement and facilitate communication. The present study draws upon the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Habitual Behaviour. This study explores the relationship between factors (performance expectancy, effort expectancy, and social influence) and Malaysian undergraduate students' habitual behaviour of using mobile phones for academic purposes. Data was collected via questionnaires from 393 undergraduate students at a Malaysian public university. The findings demonstrated that effort expectancy and social influence had a significant relationship with mobile phone habitual behaviour for academic purposes. However, performance expectancy had no significant relationship with mobile phone habitual behaviour for academic purposes. This study sheds light on the critical role of effort expectancy and social influence in shaping students' habitual behaviour regarding academic mobile phone usage.